Assessment of lifestyle changes related to quarantine among Saudi population during the early COVID-19 pandemic: pre- and post-analysis - Mira M. Abu-Elenin; Ahmed A. Elshora; Marwa A. Shahin; Nesrin K. Abd El-Fatah (SpringerOpen, 2024)
Abstract Background The escalating emergence of the COVID-19 pandemic interrupted human life due to the ever-increasing morbidity, containment measures, and the associated emotional distress. This study examined the influence of COVID-19-related measures on the lifestyle behaviors of adults living in the Kingdom of Saudi Arabia (KSA). Methods The study recruited 638 participants through convenience sampling in Jeddah and Taif cities, Saudi Arabia. Demographic characteristics and COVID-19-related information were collected through an anonymous self-reported electronic questionnaire. Lifestyle behaviors were assessed before and during the quarantine using the Healthy Dietary Habits Index (HDHI)-A and the International Physical Activity Questionnaire (IPAQ-SF). Results The study revealed significant changes in the dietary pattern: a reduction in fish intake and increased consumption of French fries and candies. Vegetables and fruit intake increased significantly. Sedentary time > 6 h per day increased from 36.7% pre to 60.8% during the pandemic. Healthy dietary index score and physical activity MET-minutes/week values were respectively 3.5% and 37.9% significantly higher before compared to the full quarantine period. Conclusion The pandemic detrimentally influenced eating habits and physical activity levels that led to weight gain, and hence higher vulnerability to COVID-19 infection and negative outcomes. This analysis provides public health agencies with data to tailor nutrition interventions that mitigate the observed adverse lifestyle behaviors.